Представленість видів червоної книги України та переліку рідкісних рослин Чернігівщини у флорі дендропарку “Тростянець” НАН України - Medvedev, V.A.; Iljenko, A.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2017)
Objective – to identify the plant species of the Red Book of Ukraine and the official list of rare plants of the Chernigiv Region in the flora of dendropark Trostjanets, the autphytosozologyсal characteristic and clarification of the nature of distribution on the territory of the dendropark. Material and methods. The object of investigation were species of the Red Book of Ukraine and official list of rare plants of the Chernigiv Region. The list of rare species is based on inventory date of 2005–2012. Results. There are 23 species of rare plants (10 tree and 13 herbaceous species), 10 species of which are listed in the Red Book of Ukraine, 10 – in the list of rare plants of the Chernihiv Region, 3 – in the Red Book of Ukraine and the list of regionally rare plants. Species of flora of the dendropark, listed in the Red Book of Ukraine, have such nature protection categories: endangered species – 3 (Hedysarum ucraіnіcum Kaschm., Spiraea polonica Blocki, Tіlіa dasystyla Steven), vulnerable – 5 (Euonymus nana Beeb., Festuca heterophylla Lam., Juniperus excelsa M.Bied., Pinus cembra L., Taxus baccata L.), rare – Betula obscura A. Kotula, unvalued – 4 species (Adonis vernalis L., Carex umbrosa Host, Galanthus nіvalіs L., Glycyrrhіza glabra L.). Conclusion. On the territory of the dendropark 14 species have unique locality (Adonis vernalis, Juniperus excelsa, Galanthus nivalis, Glycyrrhiza glabra, Hypericum montanum L., Hedysarum ucrainicum, Potentilla alba L., Centaurium erythraea Rafn, Scilla bіfolia L ., Carex lіmosa L., Tіlіa dasystyla, Spіraea polonіca, Cerasus frutіcosa Pall. and Euonymus nana). Rare species are Alnus іncana (L.) Moench, Anemone sylvestrіs L., Betula obscura, Carex umbrosa, Fragarіa moschata Duch., Pinus cembra, Taxus baccata, often – Junipers communis L., everywhere – Festuca heterophylla.